RESEARCH METHOD AND VARIABLE IN FINISHING STUDY DURING PANDEMIC TIME FOR ENGLISH LANGUAGE AND EDUCATION STUDENTS - Sri Handayani Marwan (LEAD (Language, Education and Development), 2022)
Purpose of the of this social service was (1) to enhance students understanding about kinds of qualitative research method; (2) To enhance students understanding about kind of research variable; and (3) to give a better solution for students who have problems in finishing their study during pandemic time. The method used in this program were lecturing, focus group discussion and consultation. Firstly, all the team delivered material to students about kinds of variable and research method also some problems that probably faced by students in conducting research during pandemics and how to overcome those problems. This meeting was conducted twice. After this meeting, we conducted focus group discussion about kind of research method and variable which are appropriate to pandemic situation. And last, they can consult to team about variable and research method. Based on the social services being conducted, it was found that students still got difficulties in choosing research method and variable, and by taking this program their can solve those problem and finally they can formulate title as well as research design which is suitable with pandemic situation. All of them choos qualitative research as the research method and online learning as the variable of the research. The novelty of this article shown at the new topic being discuss since it was happening and new phenomena in university education. Hopefully, the result of this study can be one of references for students who want to finish their study effectively in this pandemic time or in online learning.